Alternative frameworks for examining Latino male bisexuality in the urban space: A theoretical commentary based on ethnographic research in Rio de Janeiro and New York. (September 2013) - Muñoz-Laboy, Miguel; Parker, Richard; Perry, Ashley; Garcia, Jonathan
Latino male bisexual experience has remained under-studied and under-theorized in much of the recent sexuality research. Based on long-term ethnographic research conducted in Rio de Janeiro and New York City, this article seeks to examine the cultural patterns and social contexts in which male bisexual experiences took shape in these urban centers, and to explore and refine a number of key theoretical formulations that have been developed in recent sexuality research. It examines the ways in which bisexual desires take shape, the choreography of sexual interactions with both male and female partners, and the continuities and changes that seem to be taking place in these settings.